2008
DOI: 10.1111/j.1462-5822.2008.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

TheLegionella pneumophilaphosphatidylinositol-4 phosphate-binding type IV substrate SidC recruits endoplasmic reticulum vesicles to a replication-permissive vacuole

Abstract: SummaryLegionella pneumophila, the causative agent of Legionnaires' disease, uses the intracellular multiplication/defective organelle trafficking (Icm/ Dot) type IV secretion system to establish within amoebae and macrophages an endoplasmic reticulum (ER)-derived replication-permissive compartment, the Legionella-containing vacuole (LCV). The Icm/Dot substrate SidC and its paralogue SdcA anchor to LCVs via phosphatidylinositol-4 phosphate [PtdIns(4)P]. Here we identify the unique 20 kDa PtdIns(4)P-binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
254
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(268 citation statements)
references
References 68 publications
13
254
1
Order By: Relevance
“…The Legionella effector SidC was such an example. SidC and its paralog SdcA were first assigned as vesicle tethering factors for promoting the recruitment and fusion of ER-derived vesicles to the bacterial phagosome (12). Recently, crystal structures of the N-terminal portion of SidC were reported (38,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Legionella effector SidC was such an example. SidC and its paralog SdcA were first assigned as vesicle tethering factors for promoting the recruitment and fusion of ER-derived vesicles to the bacterial phagosome (12). Recently, crystal structures of the N-terminal portion of SidC were reported (38,40).…”
Section: Discussionmentioning
confidence: 99%
“…SidC and its paralog SdcA have been shown to recruit ER vesicles to the LCV (12). We thus investigated the relevance of the E3 ligase activity of SidC in Legionella infection.…”
Section: Ubiquitin Ligase Activity Of Sidc Is Required For the Recruimentioning
confidence: 99%
See 1 more Smart Citation
“…127 SidC and its paralog SdcA, identified in L. pneumophila, are capable of recruiting the ER-derived vesicles to build LCV. 128 A new study showed that SidC/SdcA is a novel type of bacterial E3 ligase with a special C46-H444-D446 catalytic triad that can form high-molecular-weight polyubiquitin chains. 129 In addition, the effector RavZ specifically deconjugates the lipid-attached LC3 marks and thereby prevents the autophagic pathway by functioning as a cysteine protease.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…It has been suggested that PI(4)P is enriched on the LCV membrane, which among other functions, anchors effectors such as SidM/DrrA, SidC, and SdcA to promote the recruitment and fusion of the endoplasmic reticulum derived vesicles with the LCV (18,19). In the amoebae host Dictyostelium discoideum, the Legionella effector protein LpnE appears to recruit the host PI-5-phosphatase OCRL to the LCV, leading to restriction of intracellular bacterial growth (20).…”
mentioning
confidence: 99%